Solving the SME finance puzzle: an examination of demand and supply failure in the UK. Issue 1 (2nd January 2023) - Owen, Robyn; Botelho, Tiago; Hussain, Javed; Anwar, Osman
ABSTRACT: Following economic instability after the Global Financial Crisis, the financing of small and medium-sized enterprise (SME) growth and productivity has become central to UK government policy for sustainable economic development, evidenced by the establishment of the British Business Bank and Regional Investment Funds. This paper considers demand-side and supply-side failures in the contemporary UK SME finance market. Adopting mixed methods, binary logit regression analysis of the 2015 UK Small Business Survey of 15, 502 SMEs is sense-checked using qualitative participatory findings from 6 SME finance support advisors. Findings confirm the importance of SME size, age, management capability and use of appropriate, timely external advice. They support the resource-based view of SME access to finance, contributing to borrower discouragement and under investment, suggesting the need for improved support to upskill entrepreneurs' financial management and investment readiness and the concept of an 'holistic entrepreneurial finance ecosystem' approach to assist UK SME finance.